The soundtrack in Brazilian animation: an analysis of Boy and the world - Carvalho, Márcia (Animus. Revista Interamericana de Comunicação Midiática, 2023)
The article aims to reflect on the importance of the soundtrack for animation. It proposes an overview of the production of Brazilian animation in search of verifying its historical evolution and a case study based on the analysis of animation O Menino e o Mundo (2014), directed by Alê Abreu. This exercise of analyzing music, sound effects and voice in animation rescues a classification of sound in three categories of Charles Sanders Peirce’s theory of signs and its application in the cinema soundtrack.